2005
DOI: 10.1111/j.1460-9568.2005.04098.x
|View full text |Cite
|
Sign up to set email alerts
|

Attention to pain localization and unpleasantness discriminates the functions of the medial and lateral pain systems

Abstract: Functional imaging studies have identified a matrix of structures in the brain that respond to noxious stimuli. Within this matrix, a division of function between sensory‐discriminative and affective responses has so far been demonstrated by manipulating either pain intensity or unpleasantness under hypnosis in two different normal volunteer groups studied on separate occasions. Our study used positron emission tomography (PET) to demonstrate this division of function under more natural conditions in a healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
206
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(214 citation statements)
references
References 90 publications
6
206
0
2
Order By: Relevance
“…It is actually difficult to provide a unique and consensual definition of the ''pain matrix'' since each area belonging to the ''pain matrix'' is not only involved in the perception of pain, but also form an ensemble of interplaying parts that cannot be reduced to a mere cortical and subcortical ''representation'' of pain. Indeed, several studies have shown that the activity of the so-called ''pain matrix'' (1) can be clearly dissociated from the perception of pain intensity [4,[35][36][37][38][39][40][41], (2) is strongly influenced by factors independent of the intensity of the nociceptive stimulus [37,39,42,43], and (3) can be evoked by nonnociceptive and non-painful stimuli [44][45][46][47][48][49]. Importantly, these experimental observations do not question the involvement of the cortical activity in the emergence of pain.…”
Section: Afferent Pathwaysmentioning
confidence: 97%
“…It is actually difficult to provide a unique and consensual definition of the ''pain matrix'' since each area belonging to the ''pain matrix'' is not only involved in the perception of pain, but also form an ensemble of interplaying parts that cannot be reduced to a mere cortical and subcortical ''representation'' of pain. Indeed, several studies have shown that the activity of the so-called ''pain matrix'' (1) can be clearly dissociated from the perception of pain intensity [4,[35][36][37][38][39][40][41], (2) is strongly influenced by factors independent of the intensity of the nociceptive stimulus [37,39,42,43], and (3) can be evoked by nonnociceptive and non-painful stimuli [44][45][46][47][48][49]. Importantly, these experimental observations do not question the involvement of the cortical activity in the emergence of pain.…”
Section: Afferent Pathwaysmentioning
confidence: 97%
“…Previous human brain imaging studies revealed that noxious heat applied to regions of the forearm elicited activation, a decrease, or a lack of modification of activity in the S1 cortex (Jones et al, 1991;Talbot et al, 1991;Apkarian et al, 1992). Recent studies showed that these discrepancies were mostly attributable to the fact that S1 activation by either tactile or painful stimuli is strongly modulated by cognitive factors, including attention, that modify somatosensory perception Rainville et al, 1997;Hofbauer et al, 2001;Kulkarni et al, 2005). Moreover, experimental manipulations specifically directed toward changing the perceived intensity, location, but not the unpleasantness of pain evoked by a noxious stimulus, significantly modulated activity in S1 (Rainville et al, 1997;Hofbauer et al, 2001;Kulkarni et al, 2005).…”
Section: Implications For Pain Perception In Human Beingsmentioning
confidence: 99%
“…First, our event-related experimental design likely minimized anticipation-related effects, which can enhance aMCC activity (Ploghaus et al, 1999;Porro et al, 2002;Nitschke et al, 2006). Second, our volunteers rated unpleasantness after each stimulus, and there is evidence that attention to the perceived unpleasantness selectively increases blood flow in pACC/sACC (but not in MCC) after painful laser stimuli (Kulkarni et al, 2005).…”
Section: Brain Regions Involved In the Observation Of Unpleasant Stimulimentioning
confidence: 99%